Computer Tomography in Comparison with Other Testing Methods Used for the Leakage Testing of HPDC Parts - Barbora, Stunova; Novotny, Filip; Prokop, Josef (Manufacturing Technology Journal, 2010)
Computer tomography could be used for non-destructive inspection of castings. This contribution deals with application of computer tomography for determination of inner quality of high-pressure die casting parts, especially in relation to leakage and compared with other testing methods. In praxis, the leakage location is identified by fracture test or by metallographic observation. Often the oxides and porosity are found. Porosity is also often found out after machining operations. This work proposes non-destructive methods of castings inspection, especially tomography, in comparison of other known and available methods, with the goal to find out the problem before machining with minimal losses.
Keywords: Pressure Tightness; Leakage; High Pressure Die Casting; Computer Tomography